2016
DOI: 10.1186/s12862-016-0679-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light environment during growth on the expression of cone opsin genes and behavioral spectral sensitivities in guppies (Poecilia reticulata)

Abstract: BackgroundThe visual system is important for animals for mate choice, food acquisition, and predator avoidance. Animals possessing a visual system can sense particular wavelengths of light emanating from objects and their surroundings and perceive their environments by processing information contained in these visual perceptions of light. Visual perception in individuals varies with the absorption spectra of visual pigments and the expression levels of opsin genes, which may be altered according to the light e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…Opsin expression patterns are known to be susceptible to variation in light conditions, especially during development (Dalton, Lu, Leips, Cronin, & Carleton, ; Fuller, Carleton, Fadool, Spady, & Travis, ; Härer, Torres‐Dowdall, & Meyer, ; Hofmann, O'Quin, Smith, & Carleton, ; Novales Flamarique, ; Sakai, Ohtsuki, Kasagi, Kawamura, & Kawata, ; Wagner and Kröger, ). For instance, teleost fish reared in murky environments where short wavelength light is rapidly scattered by suspended particles, or in red light enriched environments, have opsin expression patterns resulting in visual sensitivities shifted toward longer wavelengths (Fuller et al., ; Härer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Opsin expression patterns are known to be susceptible to variation in light conditions, especially during development (Dalton, Lu, Leips, Cronin, & Carleton, ; Fuller, Carleton, Fadool, Spady, & Travis, ; Härer, Torres‐Dowdall, & Meyer, ; Hofmann, O'Quin, Smith, & Carleton, ; Novales Flamarique, ; Sakai, Ohtsuki, Kasagi, Kawamura, & Kawata, ; Wagner and Kröger, ). For instance, teleost fish reared in murky environments where short wavelength light is rapidly scattered by suspended particles, or in red light enriched environments, have opsin expression patterns resulting in visual sensitivities shifted toward longer wavelengths (Fuller et al., ; Härer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of electroretinogram (ERG) and behavioural optomotor responses supporting enhanced sensitivity to the longer wavelength rearing spectrum in M. atlanticus (Schweikert & Grace, ), P. reticulata (Sakai et al, ) and cichlids (Smith et al, ), respectively, there is no evidence that reported plastic changes in opsin gene expression have any relevance for the visual capabilities of other fishes. Even the study on M. atlanticus (Schweikert & Grace, ) is hard to interpret as there was no control group examined, preventing any assessment of natural variation in opsin expression and ERG responses during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Besides genetically programmed opsin switches that occur during retinal development, studies on black bream Acanthopagrus butcheri (Munro 1949) (Shand et al, ), cichlids (Dalton et al, ; Härer et al, ; Nandamuri et al, ), bluefin killifish Lucania goodei Jordan 1880 (Fuller & Claricoates, ), guppies Poecilia reticulata Peters 1859 (Sakai et al, ) and Atlantic tarpon Megalops atlanticus Valenciennes 1847 (Schweikert & Grace, ) have shown plasticity in opsin gene expression in response to changes in the light environment. In guppies (Sakai et al, ) and the M. atlanticus (Schweikert & Grace, ), which seem to upregulate opsin gene products to match the dominant wavelengths of new spectral backgrounds, behavioural and electroretinogram observations suggest enhanced sensitivity to the prevalent spectrum. In contrast, both adult (Novales Flamarique et al, ) and developing (Rennison et al, ) threespine sticklebacks Gasterosteus aculeatus L. 1758 show minute, if any, plasticity in opsin expression and the same appears to be the case for other species including Atlantic molly Poecilia mexicana Steindachner 1863 (Tobler et al, ) and Atlantic cod Gadus morhua L. 1758 (Valen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the relative signal received by cones expressing LWS opsins compared to those expressing RH2 opsins (the next shortest class), the red/orange colors may be perceived as brighter. Indeed, Sakai et al (2016) recently showed that guppies with higher LWS expression have a greater sensitivity to orange light. Furthermore, expression of LWS opsins has been shown to co-vary with mate preferences for orange male coloration across natural populations in Trinidad (Sandkam et al 2015a).…”
Section: Mate Choice and Dietary Carotenoidsmentioning
confidence: 99%
“…Traditionally, color vision was thought to only vary across species, but recent work in several taxa has found that color vision can also vary across populations [e.g., bluefin killifish (Fuller et al 2004), cichlids , stickleback (Flamarique et al 2013), guppies and close relatives (Sandkam et al 2015a, b)] which can be due to both genetic variation and plasticity (Fuller et al 2005;O'Quin et al 2012;Ehlman et al 2015; reviewed in Carleton et al 2016). Several studies have recently shown that visual systems are plastic with respect to developmental stage, time of day, and lighting environment (Fuller and Claricoates 2011;Johnson et al 2013;Flamarique et al 2013;Dalton et al 2015;Ehlman et al 2015;Sakai et al 2016).…”
Section: Introductionmentioning
confidence: 99%